Effect of General and Spinal Anesthesia on Hepatic and Renal functions and Hemodynamic parameters of Iraqi Women Undergo Cesarean Section: Comparative Study - Ola K. Mohammed; Mustafa Ghazi Alabbassi; Alaa Abdul-Mehdi Aldujaili; Dalia Abd Alkader Shakoor; Mohanned Mohammed Bakir Almoossawi (College of Pharmacy / Mustansiriyah University, 2018)
Both general and spinal anesthesia can be use during caesarean section. Spinal anesthesia is preferred by anesthesiologists and gynecologists because of its beneficial effects for both mothers and their fetuses. They were not affecting the creatinine level but affecting only on elevation of liver enzymes. Spinal anesthesia effect on hemodynamic parameters more than general anesthesia, and it causes less operative blood loss than general anesthesia.